Recurrent Oral Mucocele Management with Diode Laser - Amira Besbes; Yamina Elelmi; Faten Khanfir; Raja Belgacem; Hichem Ghedira (Case Reports in Dentistry)
Background. Mucocele is the most common minor salivary glands disease. Its management may present a challenge for dental professionals. The aim of the present clinical case was to describe mucocele treatment with diode laser and its benefits. Case Report. A case of lower lip mucocele in a 10-year-old female patient is reported. A conventional excision surgery was performed. Two months later, the patient reported discomfort and swelling at the same operative site. The lesion had recurred. Thus, mucocele was removed using a diode laser with wavelength of 980 nm, an initiated fiberoptic tip of 300 μm, in continuous mode, and a power setting of 2 Watts. The procedure was rapidly completed with no bleeding. The patient was followed-up after 2 weeks and 6 months. The wound healed without complications: no postoperative discomfort or pain and no infection. There was no recurrence. Conclusion. Diode laser is an effective, easy, bloodless, and well-accepted procedure to treat mucocele in pediatric patients.